Magnesium Nanoparticles With Pd Decoration for Hydrogen Storage - Liu, Yana; Zhu, Jinglian; Liu, Zhibing; Zhu, Yunfeng; Zhang, Jiguang; Li, Liquan (Frontiers in Chemistry, 2020)
In this work, Magnesium nanoparticles with Pd decoration, ranging from 40 to 70 nm, were successfully coprecipitated from THF solution, assined as the Mg-Pd nanocomposite. The Mg-Pd nanocomposite exhibits superior hydrogen storage properties. For the hydrogenated Mg-Pd nanocpmposite at 150 oC, the onset dehydrogenation temperature is significantly reduced to 216.8 oC, with a lower apparent activation energy for dehydrogenation of 93.8 kJ/mol H2. High content γ-MgH2 formed during the hydrogenation process, along with PH0.706 contributes to the enhancing of desorption kinetics. The Mg-Pd nanocomposite can take up 3.0 wt% hydrogen in 2 h at temperater low as 50 oC. During lower hydrogenation tempeatures, Pd can dissociate hydrogen and create a hydrogen diffusion pathway for the Mg nanopaticles, leading to the decrease of the hydrogenation apparent activation energie (44.3 kJ/mol H2). In addition, the Mg-Pd alloy formed during hydrogenation/dehydrogenation process can play an active role in the reversible metal hydride transformation, destabilizing the MgH2.